Building a New Life in Australia: The Longitudinal Study of Humanitarian Migrants - Findings from the first three waves - Department of Social Services (Department of Social Services, 2020)
The report provides information about a wide range of topics related to the settlement outcomes of humanitarian migrants who arrived in Australia in 2013. It examines their lives in the first three years of life in Australia.
Keywords: Life Events; Culture -- Culturally and Linguistically Diverse; Culture -- Immigrants; Satisfaction; Education and Training; Health; Employment; Disadvantage, adversity and resilience; Labour market; Migration and settlement; Health; Employment; Education and Training; Culture; Life Events; Satisfaction; Culturally and Linguistically Diverse; Immigrants; Adversity and resilience; Employment and unemployment; Migration and settlement; Dsiadvantage, adversity and resilience